2015
DOI: 10.1038/srep16142
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D supplementation on insulin and glucose metabolism in overweight and obese individuals: systematic review with meta-analysis

Abstract: The aim of this systematic review was to assess the effect of vitamin D supplementation on glucose and insulin metabolism in overweight and obese subjects. The search process was based on the selection of publications listed in the databases: PubMed, Scopus, Web of Knowledge, Embase and the Cochrane library that met the inclusion criteria. Twelve randomized controlled trials were included. The analysed population consisted of 1181 individuals with BMIs >23 kg/m2. Changes in the concentration of 25(OH)D, fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 50 publications
(198 reference statements)
2
65
1
1
Order By: Relevance
“…In this study, we investigated the relationship between vitamin D and DPN at different ages. The results showed that vitamin D was only associated with DPN in the elderly patients but not in young and [18][19][20] but not to improve blood glucose 21 and endothelial function. 22 Schwann cells are peripheral glial cells that synthesize and secrete various growth factors, such as nerve growth factor (NGF), insulinlike growth factor (IGF), ciliary neurotrophic factor (CNTF), and neurotrophin-3 (NT-3), and these growth factors play an important role in nerve damage and repair.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In this study, we investigated the relationship between vitamin D and DPN at different ages. The results showed that vitamin D was only associated with DPN in the elderly patients but not in young and [18][19][20] but not to improve blood glucose 21 and endothelial function. 22 Schwann cells are peripheral glial cells that synthesize and secrete various growth factors, such as nerve growth factor (NGF), insulinlike growth factor (IGF), ciliary neurotrophic factor (CNTF), and neurotrophin-3 (NT-3), and these growth factors play an important role in nerve damage and repair.…”
Section: Discussionmentioning
confidence: 84%
“…Regarding the mechanism involved, vitamin D deficiency can affect glucose metabolism by impairing islet β‐cell function, reduce neurotrophic factors causing neurological dysfunction, and attenuate anti‐inflammatory effects leading to vascular endothelial dysfunction and supporting the development of atherosclerosis, thereby promoting the occurrence and development of DPN . However, studies on vitamin D supplementation for DPN have been shown to improve DPN neuropathic pain and affect DPN development by repairing and protecting nerves but not to improve blood glucose and endothelial function …”
Section: Discussionmentioning
confidence: 99%
“…Although without significance, our results showed a positive correlation between VD and HDL-c levels. Sriram et al [34] and Prodam et al [35] showed that VD levels are negatively correlated with total cholesterol, Contradicting recent studies that have shown that supplementation with VD may improve glycemia and lipid profile in children with deficiency of this vitamin [36] [37] [38], Jamka et al [39] and Jamka et al [40] performed meta-analysis that showed no correlation between VD and glucose and lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Other contrasting meta-analysis of 15 trials did not find sufficient evidence to recommend vitamin D supplementation for improving glycemia or insulin resistance in obese patients with diabetes, normal fasting glucose levels, or impaired glucose tolerance [67].…”
Section: Diabetesmentioning
confidence: 96%